The Use of ChatGPT in Academic Writing Skills for EFL Learners: A Systematic Literature Review - Ni Putu Yunda Kirana; Santosa, Made Hery (Fakultas Ilmu Budaya, Universitas Brawijaya, 2024)
In today’s digital era, technology greatly affects education, especially in learning English as EFL. This systematic review aims to analyze and summarize various previous studies related to the use of ChatGPT in academic writing for EFL learners. The study used PRISMA to obtain results. The study was carried out by reviewing fourteen articles published between 2023 and 2024. The selection process follows a systematic method, in accordance with the inclusion and exclusion criteria set. The results show that the use of ChatGPT has a positive impact on students' writing skills. ChatGPT can improve students' writing performance in terms of grammar, text coherence, and formulating ideas. Previous studies have agreed that ChatGPT provides personalized feedback, increases motivation, and supports student-centered learning. However, there are still concerns about academic integrity and creativity. Therefore, the practical implication of this study is that teachers are advised to support students' writing skills with clear goals while still carefully considering ethics.